Probiotics and Oxidative Stress - Xin Zhao (Probiotics and Oxidative Stress, 2022)
The problem of population aging is becoming more and more serious. Looking for anti-aging active substances and studying their anti-aging mechanism has been a research hotspot in recent years. As a potential anti-aging substance, probiotics have the advantages of high safety, wide source of strains, easy availability and low cost. From birth to aging and death, probiotics of intestinal flora are always in the process of dynamic change. After the baby was born, bacteria quickly colonized in the intestine, first of all aerobic bacteria such as Escherichia coli and Streptococcus. After one week, the number of aerobic bacteria decreased and the number of Bifidobacteria increased, becoming the main strain. From childhood to adulthood, the intestinal flora forms a relatively stable flora structure after the gradual increase in the number of Lactobacillus and Bacteroides and the slight decrease in the number of Bifidobacteria. After aging, the number and species of Bifidobacteria and Bacteroides decreased significantly, the number of facultative anaerobic bacteria such as Clostridium and Clostridium putrefaciens increased significantly, and the intestinal flora showed diversity. With the aging of the body, the intestinal flora will change, the Bifidobacteria and Bacteroides in the intestinal flora will gradually decrease, while the Clostridium and Clostridium putrefaciens will gradually increase. Probiotics, as the beneficial bacteria to the host in the intestinal flora, can affect the intestinal flora and delay aging. This book studies probiotics from different sources, and expounds their antioxidant effect and mechanism.